Answer:
A
Step-by-step explanation:
because it'll have positive x and y intercepts
Answer:
a = 29
u = 12
Step-by-step explanation:
32 + 7u + 9 + 2a - 3 = 3a + 7u + 9
32 + 2a - 3 = 3a
a = 29
3(29) + 7u + 9 = 180
7u = 180 - 96
7u = 84
u = 12
Answer:
The remainder is -2.
Step-by-step explanation:
According to the Polynomial Remainder Theorem, if we divide a polynomial P(x) by a binomial (<em>x</em> - <em>a</em>), then the remainder of the operation will be given by P(a).
Our polynomial is:
![P(x) = x^3-4x^2-6x-3](https://tex.z-dn.net/?f=P%28x%29%20%3D%20x%5E3-4x%5E2-6x-3)
And we want to find the remainder when it's divided by the binomial:
![x+1](https://tex.z-dn.net/?f=x%2B1)
We can rewrite our divisor as (<em>x</em> - (-1)). Hence, <em>a</em> = -1.
Then by the PRT, the remainder will be:
![\displaystyle\begin{aligned} R &= P(-1)\\ &=(-1)^3-4(-1)^2-6(-1)-3 \\ &= (-1)-4(1)+(6)-3 \\ &= -2 \end{aligned}](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cbegin%7Baligned%7D%20%20R%20%26%3D%20P%28-1%29%5C%5C%20%26%3D%28-1%29%5E3-4%28-1%29%5E2-6%28-1%29-3%20%5C%5C%20%26%3D%20%28-1%29-4%281%29%2B%286%29-3%20%5C%5C%20%26%3D%20-2%20%5Cend%7Baligned%7D)
The remainder is -2.
Answer:
6
Step-by-step explanation:
find a common factor
6*8=48
8*6=48
Answer:
x=3, y=5
Step-by-step explanation: